Real-world clinical outcomes of EKOS catheter-directed thrombolysis versus systemic alteplase in acute pulmonary embolism: a retrospective cohort study - Senosy, Tarek Mahmoud; Elsayed, Asmaa A.; Abd Razik, Eman Fathi; Mosa, Tarek Khairy; Ali, Ahmed Mahmoud; Ibrahim, Ahmed R. N.; Mohamed, Osama Nady; Wahsh, Engy A. (Frontiers in Pharmacology, 2026)
BackgroundThe use of EkoSonic Endovascular System (EKOS) that combines ultrasound technology with catheter-directed thrombolysis has shown promising outcomes in patients with pulmonary embolism (PE) in dissolving clots effectively. This method targets thrombus removal precisely, minimizing systemic exposure to thrombolytic agents and thereby reducing bleeding risks. Given its minimally invasive approach and focused delivery, EKOS offers a safer alternative for intermediate high-risk patients in whom traditional anticoagulation or systemic thrombolysis may pose higher risks of complications. This study compares the safety and effectiveness of EKOS versus intravenous (IV) alteplase infusion in managing acute PE.MethodsA retrospective cohort study was conducted at a tertiary care hospital, examining patient records from 2022 to 2024 according to predefined eligibility criteria. Individuals aged 18 years or older diagnosed with intermediate- to high-risk PE, who showed clinical deterioration after 48 h of anticoagulation, were enrolled, as assessed by the National Early Waning Score (NEWS). Patients were excluded if they had a stable PE or were at a high risk of hemodynamic decompensation at the time of presentation. The primary outcomes were the change in tricuspid annular plane systolic excursion (TAPSE) and right ventricular-to-left ventricular (RV/LV) diameter ratio from baseline to 1-week outpatient follow-up.ResultsOut of 104 eligible patients, 54 received EKOS (EKOS group) and 50 received IV alteplase infusion (control group). The RV/LV diameter ratio significantly decreased, while TAPSE improved significantly in the EKOS and control groups. At the end of follow-up, the incidence of major bleeding events within 72 h was significantly lower in the EKOS group (2 vs. 8; p = 0.03). Although all-cause mortality at 6 months was lower in the EKOS group, the difference was not statistically significant (p = 0.3).ConclusionEKOS showed comparable efficacy to systemic thrombolysis, reducing right heart strain, improving RV function, and minimizing complications in patients with intermediate- to high-risk PE after failed anticoagulation, with deterioration in clinical condition and the need for rescue thrombolysis. In addition, EKOS had a lower incidence of major bleeding within 72 h, making it a safer option for rescue thrombolysis.